2019
DOI: 10.1016/j.neuint.2019.05.004
|View full text |Cite
|
Sign up to set email alerts
|

N-(3-Ethoxy-phenyl)-4-pyrrolidin-1-yl-3-trifluoromethyl-benzamide (EPPTB) prevents 3-iodothyronamine (T1AM)-induced neuroprotection against kainic acid toxicity

Abstract: Thyroid hormone and thyroid hormone metabolites, including 3-iodothyronamine (T1AM) and 3-iodothyroacetic acid (TA1), activate AKT signaling in hippocampal neurons affording protection from excitotoxic damage. We aim to explore whether the mechanism of T1AM neuroprotection against kainic acid (KA)-induced excitotoxicity included the activation of the trace amine associated receptor isoform 1 (TAAR1), one of T1AM targets. Rat organotypic hippocampal slices were exposed to vehicle (Veh) or to 5 μM kA for 24 h in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Activation of these pathways may, in part, increase the ability of neuronal cells to survive toxic insults such as the excitotoxic treatment that was mimicked by exposing hippocampal slices to NMDA and kainic acid. In this study, NMDA and kainic acid consistently induced death of neurons of the CA1 and CA3 regions of organotypic hippocampal slices, which correlated to the reduced hippocampal levels of p-Akt that we have previously observed [32] but also of p-Erk1/2. In the presence of the both extracts, NMDA- and kainate-induced cell death was reduced and, in parallel, the levels of p-Akt and p-Erk1/2 remained high in the hippocampus.…”
Section: Discussionsupporting
confidence: 84%
“…Activation of these pathways may, in part, increase the ability of neuronal cells to survive toxic insults such as the excitotoxic treatment that was mimicked by exposing hippocampal slices to NMDA and kainic acid. In this study, NMDA and kainic acid consistently induced death of neurons of the CA1 and CA3 regions of organotypic hippocampal slices, which correlated to the reduced hippocampal levels of p-Akt that we have previously observed [32] but also of p-Erk1/2. In the presence of the both extracts, NMDA- and kainate-induced cell death was reduced and, in parallel, the levels of p-Akt and p-Erk1/2 remained high in the hippocampus.…”
Section: Discussionsupporting
confidence: 84%
“…The neuronal degeneration mediated by KA involves ER stress and the activation of ER sensors [45]. In organotypic hippocampal slices, KA induces a selective death in the CA3 region [27,28,46]. We observed that at a concentration of 10 or 20 µM, TQ was able to reduce neuronal damage induced by KA (Figure 2F).…”
Section: Discussionmentioning
confidence: 78%
“…KA triggers a delayed type of excitotoxic cell death in the CA3 area of organotypic hippocampal slices through activation of ionotropic glutamate receptors [27,28]. Additionally, it has been shown that KA induces cell death through caspases activation [29], increase expression of pro-apoptotic proteins, such as Bim and Bax, which lead to a decrease in the Bcl-2-Bad ratio, paralleled release of cytochrome c and cleavage of poly(ADP-ribose)polymerase (PARP) [30].…”
Section: Discussionmentioning
confidence: 99%
“…When administered to rodents, T1AM induces neurological and metabolic effects similar, but also opposite to those induced by T3. Among these, T1AM activates neuroprotective signaling including the activation of the AKT and PKA signaling [2,3]; it stimulates neuronal plasticity [4,5] and induces central-mediated reduction of body temperature without activating the brown adipose tissue [6][7][8]. Most of the pharmacological effects of T1AM, including the effect on body temperature, have been described following acute administration of the amine.…”
Section: Introductionmentioning
confidence: 99%